Effectiveness of an Instructional Program on knowledge and of attitudes regarding environmental cleaning among of housekeeping staffs in AL-Rushfa teaching Hospitals in Bagdad City″ - Karim Jabr, Marwa; Alwan Mansour, Khalida (International Journal of Psychosocial Rehabilitation, 2020)
Objective(s): This study aims to determine the effectiveness of the instructional program on housekeeping staff knowledge and attitudes related to environmental cleaning, and to find out the association between the effectiveness of the program with age, gender, level of education, years of service, training session and opinion about the training session Methodology: A quasi-experimental design, using two groups pre and post-test approach is carried throughout the present study. The study was carried out at Al-Rusafa Teaching Hospitals in Baghdad city for the period from February 2nd to March 2nd 2020. The study included a non-probability purposive sample of (60) housekeeping staff who are working in Ebn Al. Nafees teaching hospital and Al-Kinndy Teaching Hospital in Baghdad City. That housekeeping staff is divided equally into (30) study and (30) control. The researcher constructed instructional program and instruments in order to reach the aims of this study, the program deals with (6) main parts related to environmental cleaning, which are (hospital hygiene, waste management, exposure to contaminated fluids and blood, hand washing, sharp and needle injuries, and warnings of infection). A self-administrated questionnaire is constructed for the purpose of the study. It is comprised of (3) parts, the first part deals with the housekeeping staff’ socio-demographic characteristics. Part II: housekeeping staff’s knowledge about environmental cleaning. Part III: the assessment of the effectiveness of an educational program on the housekeeping staff`s` attitude related to environmental cleaning. Results The results of the current study revealed that most of the housekeeping staff were male and at age under 30 years old and most of them have primary school graduates. The results revealed that housekeeping staff who participated in instructional program demonstrated a low level of knowledge before the implementation of an instructional program and the level of knowledge improves with a high level after the implementation of an instructional program related to all domains. There is a significant difference in the study group level of knowledge and attitude before and after implementation of the program. There are no significant statistical associations between the level of knowledge and attitude of the study group at the post-test period and their demographic characteristics. Recommendations: Implementation of the instructional program about the prevention of infection in the hospital and improve the knowledge of housekeeping staff about hospital hygiene and infection control.